2019
DOI: 10.1089/jwh.2017.6884
|View full text |Cite
|
Sign up to set email alerts
|

Rural–Urban Residence and Stage at Breast Cancer Diagnosis Among Postmenopausal Women: The Women's Health Initiative

Abstract: Future studies should examine other potential effect modifiers to identify novel factors predictive or protective for late stage at breast cancer diagnosis associated with rural-urban residence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…9,[59][60][61][62] In contrast, other studies have shown that rurality or travel distance have an inverse or no association with late diagnosis. 6,14,63,64 In several countries, rural regions tend to have more socio-economic disadvantage than urban regions. [65][66][67] Moreover, other studies have found that rural regions have higher prevalence of physical inactivity, obesity, smoking, alcohol consumption, and chronic diseases, often related to socio-economic deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[59][60][61][62] In contrast, other studies have shown that rurality or travel distance have an inverse or no association with late diagnosis. 6,14,63,64 In several countries, rural regions tend to have more socio-economic disadvantage than urban regions. [65][66][67] Moreover, other studies have found that rural regions have higher prevalence of physical inactivity, obesity, smoking, alcohol consumption, and chronic diseases, often related to socio-economic deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies that have assessed rural/urban differences have found that rural patients present with more advanced disease stage . In contrast, other studies have shown that rurality or travel distance have an inverse or no association with late diagnosis …”
Section: Discussionmentioning
confidence: 99%
“…30 U.S. Census tracts provide more granular information about neighborhoods than larger county definitions. 11 Study participant addresses were geocoded as previously described, [31][32][33] and assigned a tract-level, RUCA code based on a reference document from the United States Department of Agriculture. 30 Our analytic sample included 155,186 women whose addresses were linkable Sealy-Jefferson, et al; Women's Health Report 2020, 1.1 http://online.liebertpub.com/doi/10.1089/whr.2020.0034 to the RUCA coding scheme £2 years after they were randomized in the clinical trials or enrolled in the observational study.…”
Section: Rural-urban Classificationmentioning
confidence: 99%
“…Socioeconomic status affects the treatment of breast cancer sufferers. Including geographic areas [25]. Residents in metropolitan areas have better disease improvement rates as well as lower mortality rates.…”
Section: Discussionmentioning
confidence: 99%